CALLICLE ED ETEOCLE - Marco Gemin (Exemplaria Classica, 2017)
Callicles in Plato’s Gorgias and Eteocles in Euripides’ Phoenissae are interrelated in several respects. Callicles’ name and character may be basically derived from Eteocles’.